Macropinosomes are a site of HIV-1 entry into primary CD4 + T cells - Tomoyuki Murakami; Ricardo de Souza Cardoso; Praveen Manivannan; Ya-Ting Chang; Eric Rentchler; Kai-Neng Chou; Yipei Tang; Joel A. Swanson; Philip D. King; Akira Ono (Proceedings of the National Academy of Sciences, 2025)
HIV-1 has been observed to enter target cells at both the plasma membrane and endosomes. However, which pathways mediate its entry into primary CD4 + T cells, the major targets of this virus, remains unclear. Here, we show that HIV-1 can enter primary CD4 + T cells through macropinocytosis, a form of endocytosis. We found that HIV-1 can enter primary CD4 + T cells at both the plasma membrane and internal compartments, while entry into common T cell lines occurred primarily at the plasma membrane. Inhibition of macropinocytosis suppressed HIV-1 internalization into and subsequent fusion with primary CD4 + T cells regardless of the viral coreceptor usage. Microscopic analysis of viral contents exposed to the cytosol confirmed that HIV-1 fusion occurs at the macropinosomal membrane. Finally, the inhibition of macropinocytosis blocked HIV-1 infection of primary CD4 + T cells. Altogether, this study identifies macropinocytosis as one pathway for HIV-1 entry into primary CD4 + T cells.